The impact of social media access and anxiety among indonesia society during covid-19 outbreak - Ifdil, Ifdil; Amalianita, Berru; Fadli, Rima Pratiwi; Zola, Nilma; Putri, Yola Eka (COUNS-EDU: The International Journal of Counseling and Education, 2021)
A novel coronavirus (2019-nCoV) outbreak began in Wuhan, China, has been named corona virus disease 2019 (COVID-19) in December 2019. The first cases of  COVID-19 was reported in Indonesia on 2 March 2020. All caused global panic, fears, anxiety  around the coronavirus have been especially amplified by social media. During coroan virus outbreak, disinformation and false reports have bombarded social media and stoked unfounded anxiety among Indonesian society. This research, therefore, aims to analyze the impact social media and anxiety level during COVID-19 outbreak in Indonesia. The procedure of this research is  Indonesian citizens old were invited to participant online survey thought Survey Monkey platform. There are 1543  participant  form aged 17 to 60 Year and form several province and region in Indonesia. The instrumen useing  the DASS was to modify patients’ anxiety. Data analyzed using JASP (Jeffrey's Amazing Statistics Program). The research showed that respondents anxiety in the very haviness category with the highest anxiety when the duration of social media access more than 6 hours in a day. The anxiety base of aspect in watching/reading  have a higher, then Imagine and  listening when access social media about corona virus among Indonesia society. Social media use is complex reading or watching  lots of news about coronavirus has led to anxiety.